Comprehensive promotion of drug traceability codes in China in 2025: challenges and solutions for tertiary outpatient pharmacists - Zhao, Zhuo; Wang, Haozheng; Zhai, Junyi; Wang, Zheng (Frontiers in Pharmacology, 2025)
Medicines are a highly regulated category of commodities that demand strict oversight across their distribution chains and face numerous challenges in ensuring safety and authenticity. In response to concerns about counterfeit products, gray-market diversion, and pressures to protect public insurance funds, China has rapidly advanced a nationwide drug traceability policy, mandating unit-level digital identifiers and requiring point-of-dispensing scanning by 1 July 2025. However, given China’s vast territory, substantial regional disparities, and complex healthcare infrastructure, this accelerated policy rollout has posed considerable challenges for frontline implementation, placing significant pressure on outpatient pharmacy operations. In high-volume tertiary hospitals, where prescription volumes are exceptionally large, the manual scanning of traceability codes has markedly increased dispensing times, prolonged patient waiting, and heightened pharmacist workloads, further complicated by inconsistent barcode placement and hardware limitations. To explore potential solutions, our team developed and evaluated a machine vision–based scanning prototype under laboratory conditions. The system demonstrated meaningful workflow improvements in simulated dispensing scenarios and holds promise for future validation and adaptation in real-world settings. Drawing on our experiences as frontline pharmacists, this study provides practical observations from a tertiary hospital in Northwestern China, examining dispensing processes before and after traceability code integration. We hope these findings contribute to international dialogue on pharmaceutical management, helping to advance medication safety, governance, and equitable access in healthcare systems worldwide.